2018
DOI: 10.3892/ol.2018.9459
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis‑related changes in iron metabolism in chronic obstructive pulmonary disease subjects with lung cancer

Abstract: Chronic obstructive pulmonary disease (COPD) is often accompanied by lung cancer. In our previous work, it was observed that matrix metalloproteinase-3 and haptoglobin (HP) polymorphisms were potential markers of enhanced susceptibility to lung cancer development among male COPD subjects. Here, results are reported on blood serum levels of several proteins involved in iron metabolism, inflammation and the oxidative stress response compared between the same groups of subjects. The blood serum levels of tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The majority of previous studies have reported positively correlated hepcidin and ferritin levels in children 38 , critical care unit patients 39 , and patients with respiratory disease 40 and vasculitis 41 . Our results studying both hypothyroid and healthy subjects are consistent with previous research.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of previous studies have reported positively correlated hepcidin and ferritin levels in children 38 , critical care unit patients 39 , and patients with respiratory disease 40 and vasculitis 41 . Our results studying both hypothyroid and healthy subjects are consistent with previous research.…”
Section: Discussionmentioning
confidence: 97%
“…31 HP polymorphism causes change in haemoglobin-bind capacity, antioxidant and iron-recycling activities, which may be important for effective oxidative stress response in lung cancer pathogenic process. 32 Specifically, in the present study, we supposed that HP and TXN2 may be involved in ferroptosis and contribute to lung cancer in Xuanwei area.…”
Section: Discussionmentioning
confidence: 69%
“…The transferrin functions to maintain cellular proliferation by providing iron for processes that have yet to be defined (Dowlati et al, 1997). A recent study demonstrated that the difference in transferrin level was significant, and its level was lower in the patients with chronic obstructive pulmonary disease (COPD) diagnosed with lung cancer (Brzóska et al, 2018). Furthermore, the results obtained by Chen et al (2017) revealed a correlation between serum transferrin levels and tumor stage in male patients and between transferrin levels and menopausal status in female patients.…”
Section: Resultsmentioning
confidence: 99%